Penerapan sistem informasi akuntansi menggunakan software microsoft excel dalam penyusunan laporan keuangan inhouse klien pada PT. Pandya Paraduta Asca - Anna Maria Bernadin Usin; Fitriana Santi (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study aims to determine how the in-house software-based Accounting Information system at PT Pandya Praduta Asca as a business actor. The subject of this research is a financial services office, namely PT. Pandya Paraduta Asca. Computer-based accounting information systems play an important role in supporting company performance. At PT. Pandya Paraduta Asca, in compiling the client's inhouse financial reports using a computer-based accounting information system with Microsoft Excel software as a data processing application, starting from drafting, data entry, processing, to the resulting output. The resulting output is in the form of financial statements. These financial statements will be used by clients for their benefit. In this case, PT X uses the financial statements for its purposes with the Bank. The application of Microsoft Excel has several advantages, namely the level of effectiveness and time efficiency is better than other applications. While the drawback is that there is no warning when a recording error occurs.